Analisis Kesesuaian Penerapan HACCP terhadap Standar Keamanan Pangan pada Industri Jasa Boga di PT. Pangansari Utama - Inayah Inayah; Erwinda Alwi Rachman; Wahyuni Sahani; Al Israq Al Israq (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
The implementation of Hazard Analysis Critical Control Point (HACCP) is a systematic approach to ensuring food safety in food service industries. The high risk of food contamination throughout food handling processes requires effective control at every stage of food management. This study aimed to evaluate the implementation of HACCP in controlling Critical Control Points (CCPs) during food production at PT. Pangansari Utama. A descriptive observational design was employed in 2025 at PT. Pangansari Utama. Observation units consisted of 66 indicators covering food selection, food storage, food processing, cooked food storage, food transportation, food serving, sanitation of ingredients and utensils, and cooking temperature-time control. Data were collected using an observation checklist developed based on HACCP principles, the Indonesian Ministry of Health Regulation No. 2 of 2023, and food service sanitation guidelines. Data were analyzed using univariate frequency distribution. The results showed that all indicators for food selection (100%), food processing (100%), cooked food storage (100%), food serving (100%), and cooking temperature-time control (100%) met the required standards. Food storage achieved 92.3% compliance, while sanitation of ingredients and utensils reached 93.3% compliance. Several non-conformities were identified in food transportation activities. Overall, HACCP implementation at PT. Pangansari Utama complied with food safety principles; however, improvements in storage systems, sanitation practices, and food transportation controls are required to strengthen risk prevention measures.